2023
DOI: 10.3390/ijerph20054314
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Degradation of OCPs Contaminated Soil by the BC/nZVI Combined with Indigenous Microorganisms

Abstract: Organochlorine pesticides (OCPs) were typical persistent organic pollutants that posed great hazards and high risks in soil. In this study, a peanut shell biochar-loaded nano zero-valent iron (BC/nZVI) material was prepared in combination with soil indigenous microorganisms to enhance the degradation of α-hexachlorocyclohexane(α-HCH) and γ-hexachlorocyclohexane(γ-HCH) in water and soil. The effects of BC/nZVI on indigenous microorganisms in soil were investigated based on the changes in redox potential and deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…However, the primary goal of this section was to evaluate the feasibility of magnetic capture in reducing the nanoparticle transport distance after the reaction. Our motivation stems from the aspiration to develop an environmental cleaning technology by using nZVI as a nanoagent for degradation of pesticides and herbicides in soil. , We fully acknowledged that implementing magnetic capture in the field, particularly for large-scale in situ applications, presents significant challenges. Given the potential to track the lateral subsurface water flow, we envisage the possibility to capture the nZVI in the water stream from agriculture areas before it reaches the nearby water bodies.…”
Section: Resultsmentioning
confidence: 99%
“…However, the primary goal of this section was to evaluate the feasibility of magnetic capture in reducing the nanoparticle transport distance after the reaction. Our motivation stems from the aspiration to develop an environmental cleaning technology by using nZVI as a nanoagent for degradation of pesticides and herbicides in soil. , We fully acknowledged that implementing magnetic capture in the field, particularly for large-scale in situ applications, presents significant challenges. Given the potential to track the lateral subsurface water flow, we envisage the possibility to capture the nZVI in the water stream from agriculture areas before it reaches the nearby water bodies.…”
Section: Resultsmentioning
confidence: 99%
“…146 Li et al suggested that the addition of nZVI can signicantly increase the dehydrogenase activity of indigenous microorganisms in soil, and thus promote the removal of organochlorine pesticides. 147 The addition of nZVI in anaerobic/anoxic/aerobic membrane bio-reactor can provide electrons for the denitrication, thus enhancing the reduction of nitrate. 148 Similarly, Zhang et al adopted biochar-supported nZVI in the cathodic removal of nitrated in a bioelectrochemical system to enhance the reduction of nitrate to NH 4 + .…”
Section: Bacterium-assisted Reduction By Nzvimentioning
confidence: 99%
“… 146 Li et al suggested that the addition of nZVI can significantly increase the dehydrogenase activity of indigenous microorganisms in soil, and thus promote the removal of organochlorine pesticides. 147 …”
Section: Bacterium-assisted Reduction By Nzvimentioning
confidence: 99%
“…This state is the first concerning indigenous in the Center-West region and the second in the self-declared indigenous population throughout the country (IBGE, 2012). Some studies address the relationship between pesticides and indigenous (LI et al, 2023;SHANKER et al, 2023;ZHU et al, 2023).…”
Section: Jenningsmentioning
confidence: 99%